Interdisciplinary-based development of user-friendly customized 3D printed upper limb prosthesis - da Silva, Letícia Alcará [UNESP]; Medola, Fausto Orsi [UNESP]; Rodrigues, Osmar Vicente [UNESP]; Rodrigues, Ana Cláudia Tavares; Sandnes, Frode Eika (Springer Nature, 2019)
This study reports on the development of a customized transradial mechanical prosthesis for a patient with bilateral transradial amputation, with a design process involving interdisciplinary project combining the areas of product design, rehabilitation, rapid prototyping, and ergonomics. The process started with clinical assessment of the patient’s characteristics, functional abilities and needs, as well as interviews exploring patient’s preferences. Next, a first version of the prosthesis was prototyped and tested, and a second phase started aiming to solve the problems and improve the prosthesis design. A second test was then executed, revealing that the second prototype utilized a more appropriate and comfortable coupling with the limb, easy activation of the hand prehension by elbow flexion and met the child’s parameters and expectations. It was possible to manufacture personalized parts for the user faster and more precisely, making them more suitable for development of discrete prostheses, which must be custom fabricated.
Keywords: 3D Printing; Assistive technologies; Design; Prosthesis